Chemical Solution Route for High‐Quality Multiferroic BiFeO3 Thin Films. Issue 9 (15th November 2019) - Yang, Bingbing; Jin, Linghua; Wei, Renhuai; Tang, Xianwu; Hu, Ling; Tong, Peng; Yang, Jie; Song, Wenhai; Dai, Jianming; Zhu, Xuebin; Sun, Yuping; Zhang, Shujun; et al.
Abstract: Bismuth ferrite (BiFeO3 ) has recently become interesting as a room‐temperature multiferroic material, and a variety of prototype devices have been designed based on its thin films. A low‐cost and simple processing technique for large‐area and high‐quality BiFeO3 thin films that is compatible with current semiconductor technologies is therefore urgently needed. Development of BiFeO3 thin films is summarized with a specific focus on the chemical solution route. By a systematic analysis of the recent progress in chemical‐route‐derived BiFeO3 thin films, the challenges of these films are highlighted. An all‐solution chemical‐solution deposition (AS‐CSD) for BiFeO3 thin films with different orientation epitaxial on various oxide bottom electrodes is introduced and a comprehensive study of the growth, structure, and ferroelectric properties of these films is provided. A facile low‐cost route to prepare large‐area high‐quality epitaxial BFO thin films with a comprehensive understanding of the film thickness, stoichiometry, crystal orientation, ferroelectric properties, and bottom electrode effects on evolutions of microstructures is provided. This work paves the way for the fabrication of devices based on BiFeO3 thin films. Abstract : Development of BiFeO3 thin films is summarized with a specific focus on the chemical solution route. An all‐solution chemical‐solution deposition (AS‐CSD) for BiFeO3 thin films with different orientation epitaxial on various oxide bottom electrodes is introduced and a comprehensive study of the growth, structure, and ferroelectric properties of these films is provided.